TEACHING COMPLEMENTARY FEEDING AND SCREENING OF TODDLER GROWTH AT OLAK KEMANG HEALTH CENTER - Harahap, Huntari; Indah Dewi Aurora, Wahyu; Hanina, Hanina; Wida, Tia; indah ayu dia, esa (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2025)
ABSTRACT Based on a micronutrient survey in 12 provinces in Indonesia, it is known that children aged 6 to 11 months consume lower nutrients than other age groups. Toddlers who do not receive complementary feeding have a 7.4-fold risk of causing stunting in children. This community service aims to increase mothers' knowledge in making the correct complementary feeding, how to give it, when to provide it, and screening the nutritional status of toddlers. Community service activities were conducted at the Olak Kemang Health Center, attended by 15 mothers and children. Based on community service, it was found that most of them were toddlers aged 30 to 36 months (60%), had the highest anthropometric status of good nutrition (standard), namely 73.33%, and the assessment of child development using the Pre-Screening Questionnaire for Development found that 93.3% of toddlers had normal development. Routine activities are needed to increase the knowledge of mothers of toddlers regarding complementary feeding and screening the growth and development of toddlers to prevent stunting. Keywords: Complementary feeding, Mother, Growth, Toddler.